ETHNOMUSIC, ETHNOPHORE, ETHNOGRAPHER - Kaztuganova Ainur; Omarova Aklima; Stamgazyev Ramazan; Karomat Dilorom; Nurbaeva Dinara (Scientific Journal of Pedagogy and Economics, 2021)
The article presents issues related to the study of the triad of «ethno music, ethnophor, ethnographer» in the axiological aspect. Their research is updated in connection with the consideration of the trinity of «ethno music, ethnophor, ethnographer» in the global world from the point of view of the spiritual and cultural values of the Kazakh people aimed to increase their importance in modern society. The necessity of theoretical understanding of the problem «ethno ear» («auditory abilities of the ethnos») is revealed - which is a common «tool» in the trinity of the concepts of ethno music, ethnophor and ethnographer, which is the rationale for such important moments related to national identity as «intonation specificity», «culture of listening / listening», « memorizing skills», «ways of articulation», etc. It is emphasized that in the course of analyzing the genres that form the basis of ethno music, it is advisable to re-examine the contribution of outstanding personalities – those people who have managed to transmit them to the present day, and those who have been able to record them. Moreover, not considering the examples, methods of upbringing, lifestyle and worldview, customs and traditions of the ancestors only as a shady of images of the distant past or book values, but working to ensure their real «return» to everyday life through the firm fixation in the minds of the younger generations. Thanks to this, one can awaken the respect for the national cultural heritage in young people. In the course of the development of these issues by genre directions, the works of domestic researchers, scientists from foreign and CIS countries were taken into account. The main theses of the article can serve in the future as a guide and necessary support for students of traditional music, secondary specialized and higher educational institutions, Master, PhD students and teachers.